Developing an Integrative Community-Based Social Health Model to Improve Quality of Life in Indonesian Primary Care: A Scoping Review - Kusumawati, Prima Dewi; Koesnadi, Koesnadi (Journal of Applied Nursing and Health, 2026)
Background: Quality of life (QoL) is influenced by health services and social determinants of health. However, evidence integrating community empowerment, social support, community health workers (CHWs), and primary health care (PHC) into a comprehensive QoL model remains limited, particularly in Indonesian PHC settings. This scoping review aimed to map current evidence and develop an integrative conceptual framework for a community-based social health model to improve QoL. Methods: The review followed PRISMA-ScR, the Arksey and O'Malley framework, Levac et al.'s enhancement, and Joanna Briggs Institute guidance. Using the Population-Concept-Context (PCC) framework, searches were conducted across five databases and relevant grey literature. Studies published between 2021 and 2026 were synthesized through systematic extraction, thematic coding, theoretical alignment, and evidence-to-framework development to generate an integrative community-based social health model for QoL improvement. Results: From 164 identified records, 50 sources were included. Five interconnected themes informed the proposed model: local needs assessment, community empowerment, social capital and social support, CHW-PHC integration, and quality-of-life-oriented evaluation. The framework's novelty lies in specifying how local assessment creates contextual fit, empowerment builds agency, social capital provides relational resources, CHW-PHC integration links social needs with services, and QoL-oriented evaluation functions as both endpoint and feedback loop. Evidence also indicated gaps in context-specific implementation studies from Indonesia, rural communities, and low-resource PHC settings, as well as limited validation using standardized QoL indicators. Conclusion: The proposed model integrates social and health-system determinants of QoL into a community-oriented PHC framework. However, empirical validation, pilot implementation, and effectiveness evaluation are needed before widespread adoption across diverse Indonesian community settings.